On the effectiveness of integrating WiMAX and Wi-Fi. (6th January 2009) - Pan, Huanxu; Yamano, Satoru; Tani, Hideaki
In this paper, we give a quantitative evaluation on the effect of integrating WiMAX and Wi-Fi, as compared to the case of separate WiMAX and Wi-Fi systems, with respect to the system capacity under QoS constraint. We focus particularly on the VoIP traffic aspects of the system. Based on this capacity evaluation, a cost analysis is further presented. We also propose and analyse a resource management scheme on Wi-Fi to WiMAX handover.